Insight into the adsorption of chloramphenicol on a vermiculite surface - Nguyen Ngoc Tri; A.J.P. Carvalho; A.V. Dordio; Minh Tho Nguyen and Nguyen Tien Trung (My University, 2018)
Insight into the adsorption of chloramphenicol on a vermiculite surface
Keywords: Chloramphenicol